Laboratory of socialist development Cold War politics and decolonization in Soviet Tajikistan - Kalinovsky, Artemy M. (Cornell University Press, 2018)
"Focusing on the Tajik Soviet Socialist Republic, this book places the Soviet development of Central Asia, and the Soviet hope for communism's bringing prosperity to a supposedly backward area, in global context"...